A Noteworthy New Species of Eriosema (Leguminosae, Papilionoideae, Phaseoleae) from Goias State, Brazil, Including an Identification Key - Fortuna-Perez, Ana Paula [UNESP]; Candido, Elisa S.; Silva, Marcos Jose da; Vargas, Wanderleia de [UNESP]; Paula Alves Bezerra, Luisa Maria de [UNESP]; Vatanparast, Mohammad (Amer Soc Plant Taxonomists, 2018)
Eriosema macrostipulatum, a noteworthy new species from Goias State, was discovered during a taxonomic study of the genus in Brazil. It is herein described, illustrated, and has its morphological and anatomical affinities with related species presented. The geographical distribution, conservation status, and information about flowering and fruiting are provided. Additionally, a dichotomous key to the taxa of Eriosema that occur in the Chapada dos Veadeiros National Park, Alto Paraiso de Goias municipality (Goias State) is provided.
Keywords: Cajaninae; cerrado; Chapada dos Veadeiros; Fabaceae; taxonomy